FL Pre-Service Teachers' Psychosocial Aspects and Educational Conditions During the COVID-19 Pandemic Lockdown - García Botero, Jacqueline; García Botero, Gustavo; Botero Restrepo, Margarita Alexandra (Íkala, Revista de Lenguaje y Cultura, 2021)
Face to the global health contingency due to covid-19, educational settings around the world have become a “research laboratory” in which technology-mediated teaching-learning processes have gained increasing importance. This research had as a main goal to identify the psychosocial aspects and educational conditions that influenced the degree of learning satisfaction of 423 students enrolled in a ba in Modern Languages (English and French) at a university in Colombia that employed technology-mediated ‘face-to-face’ learning (pat, as per its Spanish acronym). Data were collected through open-ended questionnaires, focus groups and participant observations, and were analyzed following the qualitative data analysis stages proposed by Miles et al., and McCracken’s (1988) coding processes. Findings show that students’ learning satisfaction is highly influenced by teacher’s support and structural conditions. These two categories have an impact on other psychosocial conditions that become a challenge for the pat technology. The results show the need for a pedagogical reflection that helps instructors unify criteria for an appropriate implementation of this methodology.